Anaesthetic management in a patient requiring one lung ventilation during COVID-19 pandemic - Teah, Ming Kai; Yap, Kent Yoon; Ismail, Abdul Jabbar; Yeap, Boon Tat (BMJ Publishing Group Limited, 2021)
Placement of a double-lumen tube to achieve one lung ventilation is an aerosol-generating procedure. Performing it on a patient with COVID-19 will put healthcare workers at high risk of contracting the disease. We herein report a case of its use in a patient with traumatic diaphragmatic rupture, who was also suspected to have COVID-19. This article aims to highlight the issues, it presented and ways to address them as well as the perioperative impact of personal protective equipment.